Mucinous tubular and spindle cell carcinoma of the kidney: a case report. - Chrysikos, Dimosthenis; Zagouri, Flora; Sergentanis, Theodoros N; Goutas, Nikolaos; Vlachodimitropoulos, Dimitrios; Flessas, Ioannis; Theodoropoulos, George; Lymperi, Maria; Birbas, Kostantinos; Zografos, George C; Mariolis-Sapsakos, Theodoros (Case Rep Oncol, 2012)
BACKGROUND: Mucinous tubular and spindle cell carcinoma (MTSC) is a rare and newly described type of renal cell carcinoma (RCC) with relatively indolent behavior. Although there are small series of this clinical entity in the literature, its histogenetic origin or line of differentiation remains unclear. PATIENTS AND METHODS: A 67-year-old woman was hospitalized for flank pain; imaging studies revealed a 6.5-cm mass in the right kidney. She was referred for fine needle aspiration of the lesion, which showed an epithelial tumor with round to oval nuclei associated with strands of metachromatic stromal tissue. Cytopathologic diagnosis was consistent with RCC. RESULTS: Subsequent right heminephrectomy was performed and the surgical pathology specimen showed an MTSC of the kidney. The patient has done well postoperatively, with 24 months of benign follow-up. CONCLUSION: A precise differential diagnosis between MTSC and other renal carcinomas (e.g. papillary RCC with sarcomatoid transformation) is important for predicting patient prognosis. Even though MTSC is a rare cause of renal masses, it should be included in the differential diagnosis, especially because its imaging might be misleading, mimicking other benign renal diseases. Heminephrectomy is the preferred treatment in these subjects.